Role of simvastatin in prevention of vasospasm and improving functional outcome after aneurysmal sub-arachnoid hemorrhage: a prospective, randomized, double-blind, placebo-controlled pilot trial. (April 2013) - Garg, K.; Sinha, S.; Kale, S. S.; Chandra, P. S.; Suri, A.; Singh, M. M.; Kumar, R.; Sharma, M. S.; Pandey, R. M.; Sharma, B. S.; Mahapatra, A. K.
Abstract Background. Vasospasm plays a major role in the morbidity and mortality after aneurysmal subarachnoid hemorrhage (aSAH). The preliminary studies suggest that statins protect against cerebral vasospasm. Objective. The aim of the study was to determine the role of simvastatin in preventing clinical vasospasm and improving functional outcome in patients with aSAH. Methods. All patients with aSAH admitted within 96 h of ictus were randomized to receive either Simvastatin or placebo – 80 mg/day for 14 days. Thirty eight patients were recruited in the study- 19 received Simvastatin and 19 placebo. All the patients underwent surgical clipping of the aneurysm. The primary outcome of the study was the development of clinical cerebral vasospasm. The secondary outcomes included Glasgow Outcome Score (GOS), Modified Rankin Scale (MRS) and Barthel Index Score (MBI) at follow-up at 1, 3 and 6 months. Results. 16% of the patients in the simvastatin group had high Middle Cerebral Artery velocities (> 160 cm/sec) on transcranial Doppler on one or more than one day during the study duration as compared to 26% of the patients in the placebo group (p = 0.70). Neurological deterioration occurred in 26% and 42% of the patients in simvastatin group versus placebo group, respectively (p = 0.31). There was an improvement in the functional outcome in the simvastatin group at 1, 3 or 6 months in the follow-up; however, this difference was not statistically significant. Conclusions. There was benefit of simvastatin in terms of reduction in clinical vasospasm, mortality or improved functional outcome, however, this was not statistically significant.